Inertial accelerated algorithms for solving a split feasibility problem - Dang, Y.; Sun, Jie; Xu, Honglei (American Institute of Mathematical Sciences, 2017)
Inspired by the inertial proximal algorithms for finding a zero of a maximal monotone operator, in this paper, we propose two inertial accel erated algorithms to solve the split feasibility problem. One is an inertial relaxed-CQ algorithm constructed by applying inertial technique to a relaxed- CQ algorithm, the other is a modified inertial relaxed-CQ algorithm which combines the KM method with the inertial relaxed-CQ algorithm. We prove their asymptotical convergence under some suitable conditions. Numerical re sults are reported to show the effectiveness of the proposed algorithms.